A juridical review of illegal parking fees based on the regional regulation of Pandeglang regency number 4 of 2023 concerning retribution and local original income - Ratu Nabilah Afifah; Mukhamad Nassir Agustiawan; Dian Samudra (Institute Of computer Science (IOCS), 2024)
Inheritance disputes arising from gifts without a deed have become a recurring issue in society, particularly due to the persistence of informal transfer practices and limited legal awareness regarding the importance of written documentation. This research is motivated by the rampant practice of illegal parking fees in Pandeglang Regency, particularly at Pasar Badak, which violates Regional Regulation Number 4 of 2023 concerning Retribution and Regional Original Revenue (PAD). Parking retribution is an important PAD source that should be managed officially and transparently by the local government through the Department of Transportation. Illegal parking not only reduces PAD but also creates legal, social, and economic problems. The study aims to identify the causes of illegal parking at Pasar Badak and examine the legal measures taken by the Department of Transportation of Pandeglang Regency. Using normative juridical and empirical juridical approaches, data were collected through interviews, field observations, and literature studies. Findings show that weak supervision, low public legal awareness, and limited official parking facilities are the main causes of illegal parking. Efforts by the Department of Transportation, such as enforcement actions and public outreach, remain sporadic and not yet effective in ensuring sustainable law enforcement. The study recommends strengthening supervision, utilizing technology through a digital parking system, and improving inter-agency coordination to maximize PAD revenue and regulate illegal parking more effectively.